Tafsir Al-Qur’an: Pemahaman Antara Teks dan Realitas dalam Membumikan Al-Qur’an - Lilik Ummi Kaltsum (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This article discusses the interpretation of the Qur’an in which the existence of the text cannot be separated from the conditions of reality. A text is very much influenced by the historicity and subjectivity surrounding it. The character and style of a text will always describe and reflect the cultural structure and mindset in which the text is formed. Likewise with the al-Qur’an, the socio-cultural conditions of the Arab community or the cultural framework of the Arab nation at that time had a lot of influence on the formation of the al-Qur'an text. The event of revelation as the starting point for the birth of the Qur’an is the key word to state that when this divine revelation was revealed to humans using the language of a certain people, namely Arabic, it indicates its historical nature. Each verse that came down was not understood as separate sentences, but were related to daily realities. The problems that arise are more caused by the clash of values ​​brought by the Qur’an with the values ​​of ancestral heritage which are deeply rooted and integrated into the life of the Arab nation. Therefore, this article tries to explore the understanding of the existence of relativity and tentativity in the interpretive field, including the interpretation of the Koran. Thus, there is no claim of truth in the world of interpretation, including the interpretation of the Qur’an by anyone, anywhere and anytime.